Effect of Synthesis Temperature on the Growth of Carbon-based Materials from Waste Engine Oil Precursor - Suhufa Alfarisa; Suriani Abu Bakar (Jurnal Penelitian Fisika dan Terapannya (JUPITER), 2019)
Different stuctures of carbon material were succesfully synthesized from waste engine oil (WEO) as carbon source using double-stage thermal chemical vapor deposition method. In this work, 5.33 wt% ferrocene was used as catalyst, precursor temperature at 450°C and the synthesis temperatures were varied from 600-1000°C with 100°C increament. The prepared samples were characterized using field emission scanning electron microscopy and micro-Raman spectroscopy. Below 700°C, amorphous structure of carbon was formed. Well growth carbon spheres were produced at 800°C while at 900°C, bigger diameter and lower crystallinity of carbon spheres were resulted. At very high temperature, 1000°C, a highly defective structure of carbon was produced. These results show that the structure of carbon materials from WEO precursor was highly affected by synthesis temperature changes